The Temporal Window of Visual Processing in Aging - He, Xianghang (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: Aging affects a variety of visual functions. In this study, we aim to quantitatively investigate the temporal characteristics of visual processing in aging. METHODS: Twelve younger (24.1 ± 1.6 years) and 12 older observers (58.4 ± 3.6 years) participated in the study. All participants had normal or corrected-to-normal vision. The contrast thresholds of the participants were measured using an orientation discrimination task with white external noise masks. The target-mask stimulus onset asynchronies were 16.7 ms, 33.4 ms, 50.0 ms, 83.4 ms, and ∞ (no external noise masks) in separate conditions. The signal stimulus was carefully chosen such that it was equally visible for the younger and older participants. An elaborated perceptual template model (ePTM) was fit to the data of each participant. RESULTS: Without masks, there was no difference in contrast thresholds between the younger and older groups (P = 0.707). With masks, contrast thresholds in the older group elevated more than those in the younger group, and the pattern of threshold elevation differed in the two groups. The ePTM fitted the data well, with the older observers having lower template gains than the younger observers (P = 3.58 × 10(−6)). A further analysis of the weight parameters of the temporal window revealed that the older observers had a flatter temporal window than the younger observers (P = 0.025). CONCLUSIONS: Age-related temporal processing deficits were found in older observers with normal contrast sensitivity to the signal stimuli. The deficits were accounted for by the inferior temporal processing window of the visual system in aging.